A Professora da Nação: as festas cívicas e as escolas na Paraíba - Ribeiro, Genes Duarte (2017)
In this work, we analyze some civic festivities that were idealized, organized and held in Paraíba in three moments of Brazilian history classically named by the political historiography: Old Republic (1889 - 1930), Era Vargas (1930-1945) and Military Regime (1964 - 1985). In this respect, our argument is based on the understanding that even though it was not the Republican regime that started the Civic Festivals, we consider that at different moments, like no other regime, it has been able to promote and promote itself through parties. Of uses of various elements such as: collective spaces; Symbolic objects; Historical contents; Rules and standards; Values and beliefs and school activities.. Thus, our objective was to investigate the pedagogical intentions of the civic parties that aimed (and still aim!) to reach the whole society through the schools, in instilling in them values and senses to be celebrated. We used as documentary sources especially the newspapers that circulated and some of them still circulate in Paraíba. In addition to the newspapers, we also consult some magazines, photographs, yearbooks, almanacs, laws, regulations, minutes and official messages prepared by the governors and forwarded to the Legislative Assembly of Paraíba. The, ordinarily published in the consulted periodicals, were of great importance for the discussion of this thesis work. From a theoretical and methodological point of view, we lead the problematization, based on the concept of representation elaborated by Chartier (1990) and, at the same time, we try to dialogue with classic and recent studies concerning the History of Education, besides having taken the historiography concerning the three Periods. Consociating the idea of representation We also use the contributions of Hobsbawn (1997); Le Goff (2003); Girardet (1987) and Catroga (2005). Finally, we affirm that the Civic Festivals were intended as well as moments of entertainment and relaxation, as it was intended to create new models of citizen republican and contribute to political propaganda around the nation and the State integrated into the school calendar and consequently, in the process of teachers and students.